Analisis Resiko Sistem Informasi Penjualan Berbasis ISO 31000: Study Kasus PT XYZ - Endang Saputra; Christ Rudianto; Penidas Fiodinggo Tanaem (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
PT. XYZ, which is engaged in the manufacture of furniture and furniture components, was established in 2006. PT XYZ in carrying out its production uses production machines that are integrated with Information Systems. In every business process carried out by PT. XYZ requires IS/IT that supports every activity it carries out. PT XYZ uses production machines that are quite old. Conditions that occur at PT. XYZ can be explained in more detail using a risk management approach. The purpose of risk management is to manage existing risks based on the ISO 31000 standard so that the company gets optimal results.